Entrevista a Luis Carlos Rodrigo Prado: Los contratos de estabilidad tributaria y su impacto en la inversión minera - Feijoo, Raúl (2014)
The interview focuses mainly on the theme of contracts Tax stability. thus, the author shows how its development has been in our system in recent years related to mining investment in our country and from the General Mining Act. He also takes a position with regard to measures to promote investment presented by the Government. Finally, the author emphasizes the importance of stability contracts primarily to provide certainty to investors.